Exploring interface phenomena - Jorge Vega Vilanova; Susann Fischer (Isogloss)
In order to choose among different methods when collecting linguistic data, many different factors should be considered. We will argue that the choice of the most appropriate methods depends on whether a construction applies within one linguistic module (e.g. syntax) or whether it applies at the interface of modules (e.g. syntax and information-structure). While Grammaticality Judgement Tasks (GJT) yield unambiguous results when applied to core-grammatical modules, they often produce inaccurate results when applied to interface-phenomena. Thus, GJTs can be used in order to distinguish between the two types of phenomena, however, in order to get reliable results concerning interface phenomena, other methods seem to be more effective – e.g. a Translation Task with elicited primed items. To demonstrate the suitability of these methods for core vs. interface phenomena, we discuss data on dative clitic doubling (an interface phenomenon) in different Spanish varieties and clitic placement and clitic doubling (core and interface phenomena) in Bulgarian Judeo-Spanish.